VÓRTICES EM TEORIAS DE CAMPO COM VIOLAÇÃO DA INVARIÂNCIA DE LORENTZ - Pereira, Carlisson Miller Cantanhede (2012)
This work addresses the effects of spontaneous Lorentz symmetry breaking on the vortex solutions of the abelian Maxwell-Higgs (AMH) model. Our model is composed by the usual AMH model where the kinetic part of the gauge field is supplemented by a non-birrefringente CPT-even term contained in the electrodynamic sector of the Standard Model extension (SME) of Colladay & Kostelecky. The work is developed in the following way: In the chapter 1, we start by doing a review about topological defects in (1+1)-dimensional scalar field theories. Based on the criterion of energy finiteness, it has been established appropriated boundary conditions for the fields. By following the well-known Bogomol nyi s method and by minimizing the system energy, we have obtained the BPS equations (first order equations) which solves the Euler-Lagrange second order equations. By last, we study the more simples topological defect, named kink, which is obtained from a λϕ4 scalar field theory. The kink solution connects two different minimum energy potencial states or vacuum s states. The second chapter is devoted to the study of stationary BPS v´ortices in field theories where abelian gauge fields are coupled to the Higgs field. The first field theory to be studied is the Maxwell Higgs model in a |ϕ|4-type potencial. Next, we study the BPS vortex solutions in a model with a pure Chern-Simons term coupled to the Higgs field (CSH), subject to a |ϕ|6-type potencial. The third and last model to be analyzed is the Maxwell-Chern-Simons-Higgs model (MCSH). To obtain charged BPS vortex in MCSH model, it is necessary to introduce a dynamical and neutral scalar field N coupled to the Higgs field in a modified |ϕ|4 which depends explicitly of the field N. In the third and four chapters, we present the original contributions of the present monograph. We study the Maxwell-Higgs model in the presence of Lorentz-violating CPT-even terms belonging to the nonbirefringent electrodynamics of the SME. The nonbirefringent SME term is composed by both parity-even and parity-odd sectors. The third chapter we shows that the parity-even LIV coefficients admit only uncharged BPS and non-BPS v´ortices in the usual |ϕ|4-potencial. Our analysis shows that the parity-even LIV parameter controls the radial thickness of the profile of the defect, which can become narrower or wider (approaching to the standard behavior of a compacton-type defect). In chapter 4, we show that the LIV parity-odd parameters allow the existence of BPS-type charged vortices if we include a neutral scalar field Ψ in the original model, the situation is similar to what occurs in the MCSH model . We use a |ϕ|4-potencial which explicitly depends in the field Ψ and its derivative.